Penerapan E-CRM Dan Analisis BEP Untuk Meningkatkan Daya Saing Produk Nugget Lele Di Pokdakan Tani Makmur - Iqbal, Muhammad; Febby Madonna Yuma; Nurhasanah; Kevin Alfarer Ginting; Zuriah Br Saragih (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2025)
Abstract: Pokdakan Tani Makmur in Asahan Regency faced low sales of fresh catfish due to intense price competition in the local market. This community service program aimed to increase the economic value of catfish farming through product diversification into catfish nuggets and the application of Electronic Customer Relationship Management (E-CRM) as a supporting tool for digital marketing. The activities included socialization, production and packaging training, implementation of social media–based E-CRM, and Break Even Point (BEP) analysis to assess business feasibility. The results showed an improvement in partners’ skills in processing and marketing catfish products. With a monthly production capacity of 30 kg, where 1 kg yields 40 pieces or 10 packs of nuggets priced at IDR 5,000 per pack, partners achieved a monthly turnover of approximately IDR 1,500,000. The BEP analysis indicated an equilibrium point at 100 kg or around three months of operation with fixed costs of IDR 1,500,000. The E-CRM system served as a supporting medium to promote products and expand market visibility, while the main factors driving sales growth were product diversification and improved quality. This activity has implications for enhancing competitiveness and economic independence among small-scale fish farming groups. Keywords: BEP; catfish nugget; diversification; E-CRM; Pokdakan Tani Makmur Abstrak: Pokdakan Tani Makmur di Kabupaten Asahan menghadapi permasalahan rendahnya penjualan lele segar akibat tingginya persaingan harga di pasar lokal. Kegiatan pengabdian ini bertujuan meningkatkan nilai ekonomi hasil budidaya melalui diversifikasi produk olahan menjadi nugget lele serta penerapan Electronic Customer Relationship Management (E-CRM) sebagai pendukung strategi pemasaran digital. Tahapan pelaksanaan meliputi sosialisasi, pelatihan produksi dan pengemasan, penerapan E-CRM berbasis media sosial, serta analisis Break Even Point (BEP) untuk menilai kelayakan usaha. Hasil kegiatan menunjukkan peningkatan keterampilan mitra dalam produksi dan pemasaran produk olahan. Dengan kapasitas produksi 30 kg per bulan, di mana 1 kg menghasilkan 40 potong atau 10 bungkus nugget dengan harga Rp5.000 per bungkus, mitra memperoleh omzet sekitar Rp1.500.000 per bulan. Analisis BEP menunjukkan titik impas pada 100 kg produksi atau sekitar tiga bulan operasional dengan biaya tetap Rp1.500.000. Penerapan E-CRM berperan mendukung promosi dan memperluas informasi produk, sementara faktor utama peningkatan penjualan berasal dari diversifikasi dan kualitas produk olahan. Kegiatan ini berimplikasi pada peningkatan daya saing dan kemandirian ekonomi kelompok pembudidaya ikan di daerah. Kata kunci: BEP; diversifikasi; E-CRM; nugget lele; Pokdakan Tani Makmur